Hispanagrama: Las ideas gramaticales en los países de la América del Pacífico - Zamorano Aguilar, Alfonso; Montoro del Arco, Esteban T.; Martínez Atienza de Dios, María; Vila Rubio, Neus (Anales de Lingüística, 2020)
-